Analisis Isi Pesan Dakwah Ustadz Das’ad Latif Dalam Chanel Youtube @Das’adlatif - Sepia Lisa; Yusuf Afandi; Desi Syafriani; Tomi Hendra (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This research is motivated by the rapid development of technology in the field of social media so that preachers use it to deliver their da'wah. Youtube is one of the social media that is loved by many people, including the younger generation who use YouTube to find the information they need, including da'wah content. This phenomenon is of concern to the preachers, one of which is ustadz Das'ad Latif, to convey the message of da'wah. The da'wah message he delivered used a distinctive language, the regional language, so that many viewers were happy with the da'wah message he conveyed. The purpose of this study is to find out the contents of Ustadz Das'ad Latif's da'wah messages on the @Das'adLatif YouTube channel. The type of research used is qualitative research, namely research that produces findings that can be achieved by using measurements of both spoken and written words. The subject of this research is the sound of da'wah messages in videos on the YouTube channel @Das'adLatif. The data collection technique for this research uses a descriptive approach by watching and recording video content. Data were analyzed by content analysis method. The results of the study show that in Ustadz Das'ad Latif's Youtube Channel there are three da'wah messages including: Aqidah messages, Sharia messages and Moral messages. The contents of the message examined on Ustadz Das'ad Latif's YouTube channel are the core of the lecture which contains da'wah messages in it. From the categories of messages that have been mentioned there are sub-categories including: messages of aqidah including: faith in Allah, faith in His Angels, faith in His book, faith in His Messenger, faith in the Day of Judgment, faith in making up the qadha and qadar. Shari'ah messages include: worship and muamalah. Moral messages include: morals to God and morals to humans.